2021
DOI: 10.1016/j.celrep.2020.108613
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Iron Metabolism and Mortality during Co-infection with Malaria and an Intestinal Gram-Negative Extracellular Pathogen

Abstract: Highlights d Co-infection with malaria and a Gram-negative bacterial pathogen leads to high mortality d Co-infection leads to elevated plasma heme and systemic bacterial persistence d Iron acquisition is critical for bacterial persistence and mortality

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
(114 reference statements)
0
1
0
Order By: Relevance
“…Besides, the mortality of malaria patients co-infected with Gram negative bacteria is up to eight times higher than in individuals with malaria monoinfection 13 . In line with this, co-infection of mice with Plasmodium chabaudi (P. chabaudi), Citrobacter rodentium and Salmonella typhimurium drive an excessive host inflammatory response and increased lethality 14,15 . Additionally, it has been demonstrated that infection with murine gammaherpesvirus 68 (MHV68) can suppress the anti-malarial humoral response to a secondary malaria infection 16 , and co-infection with hepatitis B virus (HBV) or dengue-infections which are prevalent…”
mentioning
confidence: 85%
“…Besides, the mortality of malaria patients co-infected with Gram negative bacteria is up to eight times higher than in individuals with malaria monoinfection 13 . In line with this, co-infection of mice with Plasmodium chabaudi (P. chabaudi), Citrobacter rodentium and Salmonella typhimurium drive an excessive host inflammatory response and increased lethality 14,15 . Additionally, it has been demonstrated that infection with murine gammaherpesvirus 68 (MHV68) can suppress the anti-malarial humoral response to a secondary malaria infection 16 , and co-infection with hepatitis B virus (HBV) or dengue-infections which are prevalent…”
mentioning
confidence: 85%